ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DITINJAU DARI GAYA BELAJAR DAN GENDER - Anwar Ardani; Charlina Nurkhafidhoh (Universitas Majalengka, 2021)
This study concerned with the low learning outcomes of grade V SDN 3 Kedungurang students in Mathematics; one of them in learning math story. The problems that arose were how students difficulties in solving math story based on learning styles and gender, how male students difficulties in solving math story according to learning styles, how female students difficulties in solving math story based on learning styles. The purpose of this study was to determine the difficulties of students in solving a matter of story based on learning styles and gender, which covered male students in learning styles and female students in learning styles. The analytical procedure used was the Newman procedure. The type of this research was qualitative research. The data collection was carried out by using questionnaires, tests, and interviews with 11 students as research subjects. The data validity test was used triangulation techniques. The results showed that first, the most dominant learning style, namely the visual learning style of 8 students, while the auditory and kinesthetic learning styles were 7 students, the three learning styles had errors according to the Newman procedure. Second, male and female students made a mistake according to the Newman procedure, namely understanding problem, transforming, calculating processes and drawing conclusions. Third, male students with visual, auditory, and kinesthetic learning styles made a mistake in understanding problems, transformations, calculation, processes and drawing conclusions. Fourth, female students made a mistake in understanding problems, transformation, calculation processes, and drawing conclusions. The solution offered to minimize students’ difficulties in solving story problems was by increasing the practice of working on story questions.